Analisis Berpikir Kritis Siswa SMP dalam Memecahkan Masalah Numerasi Ditinjau dari Persepsi Diri terhadap Kompetensi Matematika - Kusumawati Indriansyah, Riandita; Firdaus, Hana Puspita Eka; Galatea, Chusnul Khotimah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze students' critical thinking skills in the context of numeracy in terms of their self-perception of mathematical competence. A qualitative approach was used with a case study design, involving four eighth-grade students at a junior high school in Bondowoso who were selected based on the categories of positive, negative, declining, and improving self-perception. The research instruments consisted of a self-perception questionnaire and numeracy questions analyzed using six indicators of critical thinking, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data were obtained through test results and interview transcripts. The results showed that students with positive and increasing self-perceptions were able to meet all six critical thinking indicators, while students with negative self-perceptions met two critical thinking indicators and students with declining self-perceptions met four critical thinking indicators. These findings indicate that positive self-perception tends to contribute to better critical thinking skills, but it was found that students with initially positive self-perception did not necessarily have high critical thinking skills. Thus, the dynamics of self-perception are an important factor that needs to be considered in the development of numeracy-based mathematics learning. Keywords: Critical Thinking, Self-Perception, Numeracy